Poisoning in children and adolescents in Kermanshah city, Iran - Mitra Hemmati; Mohamad Reza Tohidi; Ali Mohammadi; Firozeh Jahanpour; Bahareh Andayeshgar; Sahar Fallah (BMC, 2024)
Abstract Background Poisoning among children and adolescents is a public health problem worldwide. To take preventive measures, the pattern of this problem should be determined. This study aimed to describe the demographic characteristics of poisoning in children and to investigate the relationship between the types of poisoning and demographic factors in children in Kermanshah province. Methods This cross-sectional, descriptive-analytical study was conducted on 250 children and adolescents under 18 years of age who were referred to Mohammad Kermanshahi Pediatric Hospital in Kermanshah province due to poisoning during 2019-2022. The demographic and epidemiological data of patients were extracted from their medical files and analyzed. Results Out of 250 cases of poisoning, 173 (69.2%) cases were unintentional, 96 (55.5%) of whom were boys. Further, 77 (30.8%) cases of poisoning were intentional, of whom 49 (63.6%) were girls. There was a significant difference between gender and intentional and unintentional poisonings (p-value = 0.005). The median age of unintentional poisoning was 3 (IQR = 2.5) and that of intentional poisoning was 14 (IQR = 2). Most cases of poisoning were in cities, 145 (83.8%) of them were unintentional and 66 (85.7%) were intentional. Most cases of intentional and unintentional poisonings occurred in spring 2017 (35.1%) and autumn 2016 (34.6%), respectively. The most common causes of poisoning were narcotics (n = 36, 34.3%) and drugs (n = 35, 33.3%) in the age group 0-3 years and drugs (n = 46, 66.9) in the age group 11-18 years. Conclusions The most common causes of poisoning were narcotics and drugs in children and drugs in adolescents. To prevent poisoning in children, parents are required to increase their knowledge of the safe storage of narcotics and drugs, such as not storing methadone in a water bottle. Targeted evaluation and preventive measures are also needed in adolescent poisoning.